Gender transversality global trends / Tendencias globales de la transversalidad de género - Ángeles Martínez Boyé (Barataria, 2013)
Since the 1980s, gender transversality broke in as an emerging object of study in the social sciences, and especially in the fields of social and political intervention. This is a time period enough to carry out a critical analysis of a process of cultural change in the sociological sense whose continuation and deepening prospects are tied, in a remarkable way, to the consequences of the financial and economic systemic crisis suffered globally since 2008 and produced by hegemonic neoliberalism.